(Table 1) Abundance of bacterioplankton and cyanobacteria in waters of the East Atlantic and Mediterranean Sea - E A Chepurnova; L G Gutveyb (PANGAEA, 1988)
Distribution of cyanobacteria as compared with total bacterioplankton was studied in the Mediterranean Sea and off the west coast of Africa in November 1985 - January 1986. Fluorescent microscopy indicated that abundance of chroococcoid cyanobacteria was 2 to 3 orders of magnitude lower than that of non-fluorescent bacteria. Cyanobacteria cells were larger than other bacterial cells and had in average 4 times larger volume. Biomass of cyanobacteria was significant percentage (5-15%) of total bacterioplankton biomass only in the surface interval (0-30 m).
Supplement to: Chepurnova, EA; Gutveyb, LG (1988): Distribution and size structure of phototrophic bacterioplankton (cyanobacteria) in the Mediterranean Sea and Atlantic Ocean. Oceanology, 28(5), 643-647